Synoptic Revision of Aspleniaceae (Asplenium, Hymenasplenium) of Rwanda - Fischer, Eberhard; Lobin, Wolfram (Phytotaxa, 2023)
Forty-four species of Asplenium and one species of Hymenasplenium are recorded for Rwanda. Three species, Asplenium markusbeckeri Eb.Fisch. & Lobin, A. ramicola Eb.Fisch. & Lobin, and A. uschiae Eb.Fisch. & Lobin are described as new to science. The new species are illustrated and their affinities are discussed. Eleven species represent new country records for Rwanda: Asplenium adiantum-nigrum var. adiantum-nigrum, A. africanum, A. boltonii, A. burundense, A. cancellatum, A. ceii, A. christii, A. inaequilaterale, A. lividum, A. trichomanes subsp. quadrivalens and Hymenasplenium kenyense. A key to all Aspleniaceae recorded from Rwanda is provided, and representative specimens from Rwanda are cited. The phytogeography of the Aspleniaceae of Rwanda is discussed. Two lectotypes are designated for Asplenium mildbraedii and A. trichomanes subsp. quadrivalens. Three species previously recorded for Rwanda (Asplenium goetzei, A. kassneri, A. lademannianum) are excluded from the flora.